1998
DOI: 10.1055/s-1998-1854
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the Dimerization of HIV-1 Protease

Abstract: Disrupting protein-protein interactions in multi-subunit enzymes is currently an underutilized mode of inhibition, and little information exists to assist the researcher in the design of agents to effect such a change within the enzyme. This work seeks to address these limitations by providing a general strategy for the design of dimerization inhibitors of the therapeutically significant enzyme HIV-1 protease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…For instance, 1 a has a remarkable K i value of 220 n M . Peptide 1 b , in which TrpOH has been replaced with PheNH 2 , is an even better inhibitor, with a threefold increase in activity 7. A key aspect of the system is the length of the tether: 14 CH 2 units appears to be the most appropriate length for placing the amino termini of the two peptides approximately 10 Å apart, which is the distance found between the N and C termini of each monomer in the enzyme 8…”
Section: Methodsmentioning
confidence: 99%
“…For instance, 1 a has a remarkable K i value of 220 n M . Peptide 1 b , in which TrpOH has been replaced with PheNH 2 , is an even better inhibitor, with a threefold increase in activity 7. A key aspect of the system is the length of the tether: 14 CH 2 units appears to be the most appropriate length for placing the amino termini of the two peptides approximately 10 Å apart, which is the distance found between the N and C termini of each monomer in the enzyme 8…”
Section: Methodsmentioning
confidence: 99%
“…Truncation of the parent compound 1 by three residues had no effect on the mechanism of inhibition, as parallel lines were also obtained for the truncated inhibitor 2. [18] This modification was also incorporated into compounds 5 and 6 in an attempt to increase potency (7 d and 8 d, respectively). In contrast, larger shifts in the slope were obtained with the smallest inhibitors 5 and 6 ( Figure 2 c), indicating a change in the mechanism of inhibition.…”
Section: Small-molecule Inhibitors Of Hiv-1 Protease Dimerization Dermentioning
confidence: 99%
“…Previous experiments in our laboratory had found that replacing the Trp-OH residue of 1 with Phe-NH 2 led to a threefold increase in HIV-1 protease inhibition. [18] This modification was also incorporated into compounds 5 and 6 in an attempt to increase potency (7 d and 8 d, respectively). With both compounds this change led to approximately a twofold increase in inhibition (Table 1).…”
mentioning
confidence: 99%